Diagnostic Utility of Laser-Doppler Vibrometry in Conductive Hearing Loss with Normal Tympanic Membrane - Rosowski, John J. (2003)
HYPOTHESIS: It was hypothesized that laser-Doppler vibrometry measurements of umbo velocity in aerated middle ears with conductive loss can differentiate ossicular interruptions, stapes fixations, and mallear fixations. More generally, we hypothesize that laser-Doppler vibrometry measurements of umbo velocity can give information about how differences in the impedance that the ossicles work against affect middle-ear function. BACKGROUND: Laser-Doppler vibrometry is a well-established research tool for exploring middle-ear function. The authors wished to investigate its potential as a clinical tool for differential diagnosis of the cause of conductive hearing loss. METHODS: Laser-Doppler vibrometry was used to investigate the relationship between the sound-induced velocity of the tympanic membrane at the umbo and the cause of conductive hearing loss when the tympanic membrane was normal and the middle ear was aerated. The results of measurements in 17 adult ears before exploratory tympanotomy were compared with the surgically determined cause of the hearing loss. The authors also measured the motion of the umbo in 10 patients who had undergone successful small-fenestra stapedectomy procedures. In all the studied ears, pure-tone audiograms were measured at the time of laser-Doppler vibrometry testing. RESULTS: There were clear statistical differences between the umbo velocity in normal ears and in ears with different ossicular pathologic conditions. There was also a clear separation of the results between ears with ossicular interruptions and ossicular fixation. The pattern of laser-Doppler vibrometry measurements in poststapedectomy ears approximated the pattern in ears with ossicular interruptions. CONCLUSION: Comparison of laser-Doppler vibrometry results and audiometry may be a sensitive and selective indicator of ossicular pathologic conditions as well as a useful tool for investigating middle ear function.